Branding Sekolah Islam Modern: Sekolah Islam Terpadu, Madrasah/Sekolah Alam, dan Tahfiz Al-Qur’an - Zainiya Anisa; Saparudin Saparudin (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2022)
Indicators of state progress can be measured based on the level of progress in the field of education. At present there is an inequality of quality in the world of Indonesian education, one of which is in Madrasah Tsanawiyah (MTs). From the data the researchers obtained, the number of private MTs dominated compared to public MTs, but their existence was not. However, in West Lombok there are several private MTs that have a good image and therefore have a good existence, including the Integrated Islamic School (SIT), natural madrasah, and tahfizul Qur'an. This study aims to determine branding carried out in Modern Islamic Schools, and what are the issues related to the implementation of branding in modern Islamic schools. The research method used is library research. The results of this study are, 1) Institutions make school characteristics. Then it was found that SDIT collaborated between science and tahfiz al-Qur'an and used public relations management. Madrasah Alam develops project-based learning with an independent learning pattern. And Tahfizul Qur'an, which makes a superior program by memorizing the Al-Qur'an, 2). Issues related to the branding of modern Islamic schools, namely students are positioned in a market orientation so that education is no longer based on knowledge and the talent needs of students, and there is a financing gap in the world of Islamic Education. Keywords: Branding, Modern Islamic School, Integrated Islamic School, Madrasah Alam, Tahfizul Qur'an Abstrak: Indikator kemajuan negara dapat diukur berdasarkan tingkat kemajuannya dalam bidang pendidikan. Saat ini terjadi ketidakmerataan kualitas dalam dunia Pendidikan Indonesia, salah satunya ada pada madrasah tsanawiyah (MTs). Dari data yang peneliti dapatkan, jumlah MTs swasta mendominasi dibandingkan dengan MTs Negeri, namun tidak dengan eksistensinya. Akan tetapi, di Lombok Barat ada beberapa MTs swasta yang memiliki image yang bagus sehingga memiliki eksistensi yang baik, diantaranya yaitu Sekolah Islam Terpadu (SIT), madrasah alam, dan tahfizul Qur’an. Penelitian ini bertujuan untuk mengetahui branding yang dilakukan di Sekolah Islam Modern, dan Apa isu terkait dengan pelaksanaan branding di sekolah Islam modern. Metode penelitian yang digunakan adalah studi Pustaka. Hasil dari penelitian ini adalah, 1) Lembaga membuat ciri khas sekolah. Kemudian ditemukan bahwa SDIT mengolaborasikan antara sains dengan tahfiz al-qur’an dan menggunakan manajemen public relationship. Madrasah Alam mengembangkan pembelajaran berbasiskan proyek dengan pola merdeka belajar. Dan Tahfizul Qur’an, yang membuat program unggulan dengan menghafalkan Al-Qur’an, 2). Isu-isu terkait branding sekolah Islam modern yaitu peserta  didik  diposisikan  pada  orientasi  pasar  sehingga  pendidikan  bukan  lagi  berbasis  keilmuan  dan  kebutuhan bakat peserta didik, dan adanya kesenjangan pembiayaan dalam dunia Pendidikan Islam.